2013
DOI: 10.1016/j.pain.2013.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on the cerebral processing of thermal pain in the human brain

Abstract: The perception of pain changes as people age. However, how aging affects the quality of pain and whether specific pain-processing brain regions mediate this effect is unclear. We hypothesized that specific structures in the cerebral nociceptive system mediate the effect of aging on the variation in different pain psychophysical measures. We examined the relationships between painful heat stimulation to the foot and both functional magnetic resonance imaging signals and gray matter volume in 23 healthy subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 87 publications
1
35
0
Order By: Relevance
“…Both experimental pain and functional neuroimaging studies have found that older people display age-related increase in the heat pain threshold [116] and reduced responses in middle insular and primary somatosensory cortices toward a 44 °C heat stimulus [117]. These age-related neuropsychological changes in pain processing may reduce older peoples’ awareness and reporting of pain that may lead to undiagnosed health problems/injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Both experimental pain and functional neuroimaging studies have found that older people display age-related increase in the heat pain threshold [116] and reduced responses in middle insular and primary somatosensory cortices toward a 44 °C heat stimulus [117]. These age-related neuropsychological changes in pain processing may reduce older peoples’ awareness and reporting of pain that may lead to undiagnosed health problems/injuries.…”
Section: Introductionmentioning
confidence: 99%
“…By accounting for differences in sensitivity to noxious thermal stimuli (Emerson et al, 2014;Erpelding et al, 2012;Grant et al, 2010;Tseng et al, 2013), ability to modulate pain (Piche et al, 2013;Stankewitz et al, 2013;Teutsch et al, 2008), as well as the amplitude of evoked cortical responses to non-noxious afferent stimuli (Fjell et al, 2007;Liem et al, 2012;Muthukumaraswamy et al, 2010), structural magnetic resonance imaging (MRI) has highlighted an important relationship between normal brain anatomy and sensory function. Based on this knowledge, we intended to address the question whether between-subject variability in cortical structure could account for differences in responses to contact heat stimulation in healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…While limited, available evidence suggests that effects of stressful experiences on dopamine-dependent learning are similar in younger and older adults (Lighthall et al, 2013). Neuroimaging studies examining primary reinforcers have shown mixed results, however, with some reporting an age-related increase in neural responses to aversive experiences (taste; Jacobson et al, 2010) and others, an age-related reduction (pain; Tseng et al, 2013). Observed differences in response to primary reinforcers are not well understood, but may be related to variability in age effects on sensory systems (Shaffer & Harrison, 2007).…”
Section: Aversive Experiencesmentioning
confidence: 99%